Surveys of U.S international finance. - Patterson, G. (Princeton Legacy Library, 2017)
Third in the series of books reporting and interpreting the policies, plans, debates, and activities involved in U.S. international finance. Prepared under the direction of Gardner Patterson by the International Finance Section, Princeton University. Published annually, in August, one year after the year covered in each volume. Originally published in 1953. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.